High-temperature oxidation reduces the bitterness of honeybush infusions depending on changes in phenolic composition. (March 2021) - Alexander, Lara; Moelich, Erika Ilette; de Beer, Dalene; Muller, Magdalena; Walczak, Beata; Joubert, Elizabeth
Abstract: Honeybush tea infusions, especially those prepared from Cyclopia genistoides, can be unacceptably bitter, given the association of this herbal tea with sweet taste. Infusions prepared from both 'fermented' (high-temperature oxidised) Cyclopia longifolia and C. genistoides contain high levels of the bitter xanthone, mangiferin, however, C. longifolia is generally less bitter than C. genistoides . The effect of phenolic changes during fermentation on the bitterness of infusions was determined for both species. Bitterness was reduced by 34–68% for C. genistoides and 55–86% for C. longifolia. Fermentation affected the phenolic composition of the two species differently, notably the ratio of mangiferin to isomangiferin remained higher for C. genistoides . Bitterness prediction models for two data sets of infusions (126 fermented and green plant material; 122 fermented plant material) including variable selection based on phenolic content gave good performance (RMSECV < 5). Nine compounds, depending on the data set, were determined to be important for the models, including xanthones, benzophenones, flavones and flavanones. Mangiferin, two tetrahydroxyxanthone-di- O, C -hexose isomers, 3-β-d -glucopyranosyliriflophenone, vicenin-2 and scolymoside were common to both models. Future application of the model would be to screen large numbers of genotypes for the breeding of selections with low bitterness potential based on phenolic composition. Highlights: Some 'fermented' C. genistoides and C. longifolia herbal tea infusions taste bitter. Oxidation ('fermentation') of plant material reduced bitterness of the infusions. Reduction in mangiferin content did not fully explain bitterness reduction. Prediction models for bitterness based on phenolic composition were constructed. The UVE-PLS models included phenolic compounds other than bitter xanthones.